Vikram and the Vampire - Natasha Sharma (New Delhi, India Zubaan, 2016)
King Vikram has a devil of a dilemma! In order to gain power and wealth beyond his wildest dreams, he must deliver a corpse to the sorcerer Shaitanish. The only problem with this simple task is that this particular corpse is home to Betal-an impish storyteller of a vampire with tricks up his sleeve. Betal gives the King a series of riddles to solve as he rides along on the King's back. If King Vikram solves the riddle, but forgets to speak his answer aloud, the vampire will continue to haunt him-spoiling his plans for innumerable riches! Nobody is quite as foolish as King Vikram and Betal runs circles around the poor man, quickly turning him into a royal punchline. Stories like this one of Vikram and Betal date back over a thousand years and in Vikram and the Vampire, Natasha Sharma brings the classic story to life in a hilarious and modern retelling. Children from eight to eighty will enjoy the tale of a dimwitted king and the tongue-twisting, punning vampire who is destined to outsmart him.
Keywords: Traditional Literature - Folktales -- Traditional Literature - Folktales